As políticas públicas de redução e prevenção dos conflitos e da violência em ambiente escolar do Estado de Mato Grosso, no período de 2003-2010, e os reflexos nas escolas estaduais do município de Cáceres - Tiellet, Maria do Horto Salles (Universidade do Vale do Rio dos Sinos, 2012)
This study presents the principles, guidelines and educational guidelines and/or security that have guided the policies of reducing and preventing violence in the school environment; identify alliances, models, speeches and underlying concepts that underpin the rapprochement between the Secretaria de Estado de Educação (SEDUC) and the Secretaria de Estado de Justiça e Segurança Pública (SEJUSP) of Mato Grosso. It discusses the theme of reducing and preventing violence in the school environment according to the theory of authors: Zygmunt Baumam and Sergio Francisco Carlos Graziano Sobrinho, which contribute with their studies for the discussion about the relationship of neoliberalism/violence and reflected in the formulation of public initiatives for reducing and preventing violence. The research is qualitative and used as data collection instruments, documentary sources and open questionnaire, the approach is anchored in Maria Cecilia Minayo. The study points to the projection of the neoliberal thought in the formulation of public initiatives of reduction and prevention of conflicts and violence in the school environment of Mato Grosso, in the period of 2003 to 2010 the SEJUSP outlined actions to schools, developing social and educational projects and programs that strengthened the presence of public safety officers in educational establishments with the justification to protect the actors and keep order of those whose were classified by the school and society as impolite,problematic and misfits. Although it had called society out to discuss the problem of violence in the school environment, SEDUC had secondary participation in drafting the security strategies, which were defined on the prism of SEJUSP, even the situations that happened in school environment weren't police case. Projects, programs and actions originating of SEDUC directed to prevention of violence in the school environment had police drawing when should be educational and pedagogical actions.
Keywords: Violência; Ambiente escolar; Conflito; Políticas públicas; Violence; School environment; Conflict; Public policy; ACCNPQ::Ciências Humanas::Educação